Effect Of Use Of Flexible Transfemoral Prosthesis On Level Of Independence In Performing Daily Activities Of Transfemoral Amputee - Nur Rachmat; Bambang Kuncoro (Jurnal Keterapian Fisik, 2022)
Background: Transfemoral amputees experience many difficulties in carrying out daily activities. One of the devices that can be used in above-knee amputation patients is transfemoral prosthesis. The use of transfemoral prostheses in post-amputation patients can help with activities, one of which is independence in self-care, mobility, and locomotion. Methods: The study was conducted at PT Kuspito Orthotic Prosthetics and the time of the study was carried out in 2021. The population of this study was users of flexible prostheses at PT Kuspito Ortotik Prosthetic. The samples of this study were flexible prostheses users at PT. Kuspito prosthetic orthotic that meets the criteria as many as 30 users. The sampling technique was purposive sampling, inclusion criteria: subjects aged 17-35 years, subjects in good health, subjects using a flexible unilateral prosthesis, at least using an artificial leg for 1 month, having a strength value of 4, having normal Range Of Motion. Exclusion criteria: the subject had advanced disease, bilateral prosthesis user. The measuring instrument used was the Functional Independence Measure (FIM) questionnaire that is valid and reliable. Results: The value of Sig. is 0.000, there is a significant difference in the level of independence between the results of the pre-test and post-test. there is a significant difference in the results that using a flexible prosthesis can increase the level of independence in above-knee amputees in carrying out daily activities. Conclusion: The functional independence of above-knee amputation patients is strongly influenced by the use of a flexible prosthesis. It is recommended that above-knee amputation patients can use a flexible prosthesis to increase the level of independence.